Biofortified Rice Expansion, Branding, and Market Linkage in Bangladesh - Ahmed, Sharif; Miajy, Abdullah; Kurishi, Alanuzzaman; Veettil, Prakashan Chellatta (International Rice Research Institute, 2024)
The CGIAR Regional Integrated Initiative Transforming Agrifood Systems in South Asia (TAFSSA) recently organized a regional workshop focused on expanding, branding, and creating market linkages for biofortified rice in Bangladesh. The workshop occurred on September 26, 2024, at the OFRD conference room, BARI, Rangpur. Approximately 45 individuals from various sectors, including government organizations such as the Bangladesh Rice Research Institute (BRRI), Bangladesh Institute for Nuclear Agriculture (BINA), the Department of Agricultural Extension (DAE), the Department of Agricultural Marketing (DAM), and Bangladesh Agriculture Development Corporation (BADC) participated in the event. Additionally, private sectors, including auto rice mills, supermarkets, traders, and seed companies, as well as cooperatives and lead farmers specializing in biofortified rice, played a vital role in the workshop.